Conjugate heat dissipation characteristics of concurrent flow of pure water/water-based nano-emulsion through a mini- and micro-channel stacked double-layer heat sink - C.J. Ho; Jr-Wei Liao; Bo-Lin Chen; Saman Rashidi; Wei-Mon Yan (Case Studies in Thermal Engineering)
The main purpose of current study is to reduce the temperature gradient and pressure drop in the heat sinks by using a new double-layer mini/micro-channel stacked heat sink. In this numerical study, the conjugate heat dissipation characteristics of concurrent flow of pure water/water-based nano-emulsion through a mini- and micro-channel stacked double-layer heat sink is investigated. The potentials of pure water/phase change nanoemulsion in a mini- and micro-channel stacked double-layer heat sink for heat dissipation are compared with those for pure water in the single-layer microchannel heat sink. The effects of different parameters, such as flow rate ratio, total flow rate, heat flux, and concentration of the phase change nanoemulsion on the heating surface temperature suppression, pressure drop ratio, thermal resistance ratio, heating surface temperature uniformity index ratio, total heat transfer coefficient gain, and performance indexes are investigated. The three-dimensional velocity field in the channel is calculated by the pseudo-vorticity-velocity method, and the finite volume method is used to discrete the mathematical formulas. The numerical results showed that when the ratio of flow rate is 0.5, the total flow rate is 25.48 cm3/min, and the heat flux is 25 W/ cm2, the overall heat transfer coefficient of the mini- and micro-channel stacked double-layer heat sink with pure water/10 % mass fraction of phase change nanoemulsion as the coolants increases by 36.14 % compared with single-layer heat sink with pure water as the coolant. In addition, when the flow rate ratio is high and the total flow rate is low, the values of average and maximum thermal resistance ratios are greater than 1.